2006
DOI: 10.1016/j.neuropsychologia.2006.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Development of cognitive control and executive functions from 4 to 13 years: Evidence from manipulations of memory, inhibition, and task switching

Abstract: Predictions concerning development, interrelations, and possible independence of working memory, inhibition, and cognitive flexibility were tested in 325 participants (roughly 30 per age from 4 to 13 years and young adults; 50% female). All were tested on the same computerized battery, designed to manipulate memory and inhibition independently and together, in steady state (single-task blocks) and during task-switching, and to be appropriate over the lifespan and for neuroimaging (fMRI). This is one of the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

102
1,493
10
74

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 1,782 publications
(1,727 citation statements)
references
References 162 publications
(188 reference statements)
102
1,493
10
74
Order By: Relevance
“…Studies tracking developmental changes in working memory and executive control show clear trajectories between 7-10 years of age, but also that children continue to demonstrate substantial improvement in these abilities beyond age 10, up to adulthood (e.g. Davidson et al, 2006;Lee et al, 2013;Zelazo et al, 2013). As such, these abilities may not be sufficiently developed in our 7-10 year-old sample to enable effective implementation of prioritization.…”
Section: Discussionmentioning
confidence: 88%
“…Studies tracking developmental changes in working memory and executive control show clear trajectories between 7-10 years of age, but also that children continue to demonstrate substantial improvement in these abilities beyond age 10, up to adulthood (e.g. Davidson et al, 2006;Lee et al, 2013;Zelazo et al, 2013). As such, these abilities may not be sufficiently developed in our 7-10 year-old sample to enable effective implementation of prioritization.…”
Section: Discussionmentioning
confidence: 88%
“…Parents might avoid demanding the impossible of their children if they knew of Michael Posner's work on the development of attentional networks 41 , which suggests that young infants can orient (direct attention) to a new item, but may not have yet developed a system to disengage, that is, voluntarily remove attention from an attended object or behavior. Similarly, it could help parents to understand that the slow and progressive development of control mechanisms during childhood 42 makes the consideration of future rewards much less likely in young children 43 . This could help parents to focus on immediate consequences when negotiating with their young children.…”
Section: R E V I E Wmentioning
confidence: 99%
“…This is due to the fact that between the ages 7 and 9 years, children acquire the cognitive flexibility needed to switch attention between different cognitive processes, such as rehearsal needed for the maintenance of information in shortterm storage and the processing of information. Davidson et al (2006) showed that flexibility in switching between goals during processing develops throughout adolescence and that adults are more adept than adolescents to regulate their rate of processing to ensure accuracy. Therefore, with development, accurate self-monitoring and flexible executive control processes compensate for the mental space required to represent them.…”
Section: The Development Of Representational Capacitymentioning
confidence: 99%